Perhitungan tarif kamar hotel menggunakan activity based costing pada Hotel Sapadia Kotamobagu - David, Rendy Julian; Ilat, Ventje; Morasa, Jenny (Indonesia Accounting Journal, 2020)
This research was conducted with purpose to compare the determination of hotel room rates by determining the cost of production issued by the company, in determining existing hotel room rates. The hotel company, named the Hotel Sapadia Kotamobagu. In this study the determination of hotel room rates will use the Activity Based Costing (ABC) method as a comparison with the room rates determination method used by the Sapadia hotel company. ABC Method Improves the accuracy of calculating goods cost by determining how much the overhead cost remain different in comparison to change other than based on production volume. The cost driver is one of the ABC elements which explain the overhead cost.